2002
DOI: 10.1084/jem.20011922
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Pathways Mediated by PA28 and hsp90 in Major Histocompatibility Complex Class I Antigen Processing

Abstract: Major histocompatibility complex (MHC) class I ligands are mainly produced by the proteasome. Herein, we show that the processing of antigens is regulated by two distinct pathways, one requiring PA28 and the other hsp90. Both hsp90 and PA28 enhanced the antigen processing of ovalbumin (OVA). Geldanamycin, an inhibitor of hsp90, almost completely suppressed OVA antigen presentation in PA28α−/−/β−/− lipopolysaccharide blasts, but not in wild-type cells, indicating that hsp90 compensates for the loss of PA28 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 36 publications
3
58
3
Order By: Relevance
“…However, short peptides bound to hsp90 which are not to be ubiquitinated are efficiently processed to be T cell epitopes in a proteasome-dependent manner (8). In addition, we found that hsp90 stimulates MHC class I epitope production from C-but not N-terminally extended short synthetic peptides (13 ϳ 22-mer) in a proteasome-dependent manner in vivo (9). Because ubiquitination of those short peptides is unnecessary to be processed by the proteasome, how hsp90 is involved in proteasome-dependent epitope production has still remained elusive.…”
Section: Cd8mentioning
confidence: 61%
“…However, short peptides bound to hsp90 which are not to be ubiquitinated are efficiently processed to be T cell epitopes in a proteasome-dependent manner (8). In addition, we found that hsp90 stimulates MHC class I epitope production from C-but not N-terminally extended short synthetic peptides (13 ϳ 22-mer) in a proteasome-dependent manner in vivo (9). Because ubiquitination of those short peptides is unnecessary to be processed by the proteasome, how hsp90 is involved in proteasome-dependent epitope production has still remained elusive.…”
Section: Cd8mentioning
confidence: 61%
“…Other studies have shown that Hsp90 inhibitors suppress MHC class I antigen processing (32). To validate these findings, we show a decrease in the expression of GOLPH2 and MHC class IB proteins by immunohistochemistry (Fig.…”
Section: Itraq-labeled Ms and Gene Expression Microarray Analysismentioning
confidence: 75%
“…Hsp90 has been proposed to be a remnant of an ancient antigen presentation system, and evidence has been presented for its involvement in MHC class I peptide processing and cross-presentation (27)(28)(29). Our results showed that Hsp90 is also required for IFN-␥-induced MHC classes I and II expression.…”
Section: Discussionmentioning
confidence: 99%